Value-centered ethics : a proactive system to shape ethical behavior - Kerns, Charles D. (HRD Press, 2005)
What?s all the fuss about ethics? Don?t all of the really bad unethical managers go to jail? Why is this relevant to me? Why should I be ethical when everyone else cheats? How can I get ahead if I am always being honest? Many managers today lack an understanding of the importance of ethical leadership in today?s organizations. Yet how managers behave is the single most important factor in determining the level of ethical behavior in an organization. No doubt you will face ethical challenges in your career?all leaders do. If you keep this book close at hand, it will help you stay on course as y.